2021
DOI: 10.1002/mar.21622
|View full text |Cite
|
Sign up to set email alerts
|

How to display products available in multiple color saturation: Fit between saturation and position

Abstract: Previous research has investigated how visual features affect the evaluation of a singular product. Less is known about the effect of visual features when multiple products are displayed. Through three pilot studies and five experiments, the current research shows that displaying lower‐saturation color on the top/left and higher‐saturation color on the bottom/right leads to a more favorable evaluation of a product available in different colors saturations. This effect occurs because the magnitude fit between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
(142 reference statements)
1
5
0
Order By: Relevance
“…Moreover, it is worth noting that the results indicate that there is no significant difference between the effect of vertical (top to bottom) or lateral (left to right) display arrangements for products displayed by green attributes. To a certain extent, our findings are consistent with previous research that has shown that the vertical or lateral display of products can elicit similar perceptual fluency and positive product attitudes (Cian et al, 2015; Huang et al, 2022; Romero & Biswas, 2016; Sundar & Noseworthy, 2014) from a fit perspective. For example, individuals have a more favorable attitude when a weight loss product advertisement shows a before (after) picture on the left (right) due to past‐left and future‐right associations (Chae & Hoegg, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, it is worth noting that the results indicate that there is no significant difference between the effect of vertical (top to bottom) or lateral (left to right) display arrangements for products displayed by green attributes. To a certain extent, our findings are consistent with previous research that has shown that the vertical or lateral display of products can elicit similar perceptual fluency and positive product attitudes (Cian et al, 2015; Huang et al, 2022; Romero & Biswas, 2016; Sundar & Noseworthy, 2014) from a fit perspective. For example, individuals have a more favorable attitude when a weight loss product advertisement shows a before (after) picture on the left (right) due to past‐left and future‐right associations (Chae & Hoegg, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that relevant research on green consumption has taken the presence or absence of green attributes in green and conventional products as the dominant attribute, and a product assortment with green alternatives can be further categorized into green and conventional products (Newman et al, 2014;Tezer & Bodur, 2020). However, there is a lack of systematic investigation on the impact of product display strategies based on the above category on green previous research that has shown that the vertical or lateral display of products can elicit similar perceptual fluency and positive product attitudes (Cian et al, 2015;Huang et al, 2022;Romero & Biswas, 2016;Sundar & Noseworthy, 2014) from a fit perspective. For example, individuals have a more favorable attitude when a weight loss product advertisement shows a before (after) picture on the left (right) due to past-left and future-right associations (Chae & Hoegg, 2013).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Thus, they differ from enhancing products used to improve positive properties (e.g., mass gainer protein powder or perfumes) that contribute to desirable situations. Because product appearance is often the first piece of information to which consumers are exposed and it helps them to make quick judgments about a product (Huang et al, 2022; Muddana, 2019; Pombo & Velasco, 2021), understanding how product visual elements affect perceived product effectiveness is important.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, our results indicate that consumers tend to infer specific information on the product based on a low‐saturation surface color: They tend to perceive the product materials as natural and believe that the product is authentic and durable. Because high‐saturation colors seem less natural than low‐saturation ones (Huang et al, 2022), consumers might indeed see products with vivid surface colors as made of less‐natural materials; analogously, because over‐saturated images are generally perceived as unnatural (Nakano et al, 2009), consumers might see vivid products as less genuine than their low‐saturation counterparts. Furthermore, and building on the documented finding that people perceive the darker version of a product as heavier and more durable (Hagtvedt, 2020), our results indicate that less‐saturated product colors (which are normally darker than their more saturated versions) can signal higher durability and lengthier product lifecycle, which is compatible with the aforementioned eco‐friendliness perception.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, when products carry a sentimental value (e.g., as in the case of gifts), consumers tend to prefer products with high‐saturation colors (Huang et al, 2023). At the same time, consumers tend to perceive high‐saturation colors as more “artificial”—and by comparison, low‐saturation colors seem more “natural” (Huang et al, 2022). For this reason, consumers tend to presume that food products presented in vivid packaging (e.g., snacks and vice food products; Kunz et al, 2020; Mead & Richerson, 2018) may negatively affect their health.…”
Section: Research Hypothesesmentioning
confidence: 99%